2007
DOI: 10.1093/tropej/fmm082
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the Detection Level of Cord Blood Thyroid Stimulating Hormone (TSH) for the Diagnosis of Congenital Hypothyroidism

Abstract: An appraisal of a 17-year primary thyroid stimulating hormone (TSH) screening programme for the detection of congenital hypothyroidism was carried out to establish the reference interval of cord blood TSH in unaffected infants; the mean cord blood TSH concentration of affected infants and the incidence of congenital hypothyroidism in the Najran province of Saudi Arabia. Our findings show a reference interval of cord blood TSH of 2.0-16.8 mU/l in unaffected infants; a mean cord blood TSH concentration of 399 mU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Therefore, relevant RIs are essential for correct test result interpretation and reducing the risk of false negatives and false positives. Failure to provide proper RIs in the pediatric population carries obvious consequences for immunochemical analytes such as TSH (8 ) and ferritin (9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, relevant RIs are essential for correct test result interpretation and reducing the risk of false negatives and false positives. Failure to provide proper RIs in the pediatric population carries obvious consequences for immunochemical analytes such as TSH (8 ) and ferritin (9 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that the use of inadequate serum ferritin reference intervals led to a substantial (Ͼ15%) underestimation of iron deficiency in low-income children (4 ). The lack of ageadjusted cutoffs for thyroid-stimulating hormone during neonatal screening for congenital hypothyroidism led to an increase in the frequency of false positives and to excessive follow-up rates (5,6 ). Mir et al (7 ) analyzed N-terminal B-type natriuretic peptide and observed age-specific sex differences, with children having concentrations up to 260% higher than those of adults.…”
mentioning
confidence: 99%
“…The average TSH cord blood levels in females and males were 10 was determined to be 1 :2,967 and 1:722 live births, respectively. The average TSH cord blood levels in females and males were 10 was determined to be 1 :2,967 and 1:722 live births, respectively.…”
Section: Resultsmentioning
confidence: 98%